Cytokeratin 8/18‐negative somatotroph pituitary neuroendocrine tumours (PitNETs, adenomas) show variable morphological features and do not represent a clinicopathologically distinct entity. Issue 3 (21st May 2021) - Soukup, Jiri; Cesak, Tomas; Hornychova, Helena; Manethova, Monika; Michnova, Ludmila; Netuka, David; Vitovcova, Barbora; Cap, Jan; Ryska, Ales; Gabalec, Filip
Abstract : Aims: In somatotroph pituitary neuroendocrine tumours (adenomas), a pattern of cytokeratin (CK) 18 expression is used for tumour subclassification, with possible clinical implications. Rare somatotroph tumours do not express CK 18. We aimed to characterise this subset clinically and histologically. Methods and results: Clinical and pathological data for the study were derived from a previously published data set of a cohort of 110 patients with acromegaly. Data included serum levels of insulin‐like growth factor 1 (IGF1), growth hormone (GH), prolactin and thyroid‐stimulating hormone (TSH), tumour diameter, tumour invasion defined by Knosp grade and immunohistochemical data concerning the expression of Ki67, p53, E‐cadherin, somatostatin receptor (SSTR)1, SSTR2A, SSTR3, SSTR5 and D2 dopamine receptor. Additional immunohistochemical analysis (AE1/3, CK 8/18, vimentin, neurofilament light chain, internexin‐α) was performed. CK 18 was negative in 10 of 110 (9.1%) tumours. One of these tumours was immunoreactive with CK 8/18 antibody, while the remainder expressed only internexin‐α intermediate filament in patterns similar to CK 18 (perinuclear fibrous bodies). CK‐negative tumours showed no significant differences with respect to biochemical, radiological or pathological features. They showed significantly higher expression of SSTR2A compared to the sparsely granulated subtype and significantly lower expression of E‐cadherin compared to the non‐sparsely granulated subtypes of tumours. The tumours showed divergent morphology and hormonal expression: two corresponded to densely granulated tumours and three showed co‐expression of prolactin and morphology of either mammosomatotroph or somatotroph–lactotroph tumours. Four tumours showed morphology and immunoprofile compatible with plurihormonal Pit1‐positive tumours. Conclusions: CK‐negative somatotroph tumours do not represent a distinct subtype of somatotroph tumours, and can be further subdivided according to their morphology and immunoprofile. Abstract :